Adverse childhood experiences and suicidal ideation in patients with major depressive disorder: investigating the mediating role of emotional reactivity and probabilistic and reinforcement learning - Somayeh Daneshvar; Jahangir Mohammadi Bytamar; Zahra Zeraatpisheh; Setareh Zand; Ali Sahraian; Laura Jobson (BMC Psychology)
Abstract Objectives Major Depressive Disorder (MDD) is a severe and widespread psychiatric condition that affects individuals globally. Suicidal ideation is one of the key symptoms associated with this disorder. Numerous studies have explored the impact of adverse childhood experiences on the development of suicidal thoughts in adulthood. However, limited research focuses on the underlying mechanisms that mediate this relationship. Therefore, the present study aimed to investigate whether emotional reactivity, along with probabilistic and reinforcement learning (PRL), serves as a mediator in the relationship between adverse childhood experiences and suicidal ideation in Iranian patients with MDD. Method The study included 201 inpatients diagnosed with MDD hospitalized in various psychiatric wards across Shiraz, Iran. Participants were selected using a convenient sampling method. Data were collected through the Probabilistic Reward Task, the Emotional Reactivity Scale, the Beck Scale of Suicidal Ideation, and the Modified Adverse Childhood Experiences – International Questionnaire. The collected data were analyzed using Pearson’s correlation test and structural equation modeling with SPSS and AMOS 26. Results Adverse childhood experiences were found to have a direct and significant relationship with suicidal ideation (p < .001). Additionally, emotional reactivity and PRL served as significant mediators in the relationship between adverse childhood experiences and suicidal ideation. Conclusion Our findings indicate that various factors—including adverse childhood experiences, emotional reactivity, and PRL—contribute to the development of suicidal ideation in patients with major depressive disorder (MDD). Therefore, it is essential to consider these factors when developing therapeutic plans.